Closing the gender leadership gap: a multi-centre cross-country comparison of women in management and leadership in academic health centres in the European Union - Kuhlmann, E; Ovseiko, P; Kurmeyer, C; Gutiérrez-Lobos, K; Steinböck, S; von Knorring, M; Buchan, A; Brommels, M (BioMed Central, 2017)
BACKGROUND: Women's participation in medicine and the need for gender equality in healthcare are increasingly recognised, yet little attention is paid to leadership and management positions in large publicly funded academic health centres. This study illustrates such a need, taking the case of four large European centres: Charité - Universitätsmedizin Berlin (Germany), Karolinska Institutet (Sweden), Medizinische Universität Wien (Austria), and Oxford Academic Health Science Centre (United Kingdom). CASE: The percentage of female medical students and doctors in all four countries is now well within the 40-60% gender balance zone. Women are less well represented among specialists and remain significantly under-represented among senior doctors and full professors. All four centres have made progress in closing the gender leadership gap on boards and other top-level decision-making bodies, but a gender leadership gap remains relevant. The level of achieved gender balance varies significantly between the centres and largely mirrors country-specific welfare state models, with more equal gender relations in Sweden than in the other countries. Notably, there are also similar trends across countries and centres: gender inequality is stronger within academic enterprises than within hospital enterprises and stronger in middle management than at the top level. These novel findings reveal fissures in the 'glass ceiling' effects at top-level management, while the barriers for women shift to middle-level management and remain strong in academic positions. The uneven shifts in the leadership gap are highly relevant and have policy implications. CONCLUSION: Setting gender balance objectives exclusively for top-level decision-making bodies may not effectively promote a wider goal of gender equality. Academic health centres should pay greater attention to gender equality as an issue of organisational performance and good leadership at all levels of management, with particular attention to academic enterprises and newly created management structures. Developing comprehensive gender-sensitive health workforce monitoring systems and comparing progress across academic health centres in Europe could help to identify the gender leadership gap and utilise health human resources more effectively.